FORMATION OF COGNITIVE GYMNASIUM STUDENTS INTEREST OF HUMANISTIC DIRECTION - I.F. Shudzikhovskaya (Academy of Cognitive and Natural Sciences, 2006)
The peculiarities of coqnitive of humane trend and ways of their forming is nevealed in the article.